Letter from Campbell Morfit to James Curtis Booth, February 10, 1851 - Morfit, Campbell (1851)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Booth about Richard Sears McCulloh (1818-1894) and his balking at selling patent rights.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Chemists; Metals--Refining; McCulloh, R. S. (Richard Sears), 1818-1894